1973
DOI: 10.1021/jm00262a003
|View full text |Cite
|
Sign up to set email alerts
|

Antiradiation agents. Substituted 2-pyridyloxy and 2-quinolyloxy derivatives of S-2-(alkylamino)ethyl hydrogen thiosulfates and 3-alkylthiazolidines and substituted 2-pyridyloxy derivatives of 2-(alkylamino)ethanethiols and corresponding disulfides

Abstract: The height of the reduction wave is proportional to the concentration of the nitrofuran compound. The logarithm of the heights was plotted against the time in a diagram of the type presented in Figure 1, from which per cent reduced compound after 1 hr reaction could be calculated. The values in Table I1 are the mean values with calculated 95% confidence limits assuming the same variation in measurements with all compounds. skilled technical assistance of Miss A. Notrman and Mr. 0. Hall (Chemistry), Mr. E. Joha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The newly appeared peak was the result of ligand as a nickel complex rather than as a mercury complex. The proposed mechanism of catalytic reduction is as follows: 1. accumulation of mercury thiolate derivative of (TC) Hg + 2TC → Hg(TC) 2 The reaction stoichiometry was determined by applying Asmus method. It was found that the ratio of (TC) : nickel is 2 : 1 (Fig.…”
Section: The Catalytic Cathodic Stripping Voltammetric Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly appeared peak was the result of ligand as a nickel complex rather than as a mercury complex. The proposed mechanism of catalytic reduction is as follows: 1. accumulation of mercury thiolate derivative of (TC) Hg + 2TC → Hg(TC) 2 The reaction stoichiometry was determined by applying Asmus method. It was found that the ratio of (TC) : nickel is 2 : 1 (Fig.…”
Section: The Catalytic Cathodic Stripping Voltammetric Methodsmentioning
confidence: 99%
“…The timonacic (TC) molecule has a biological significance; its importance arises from the fact that the thiazolidine ring is an integral part of pharmacologically active compounds like penicillins and antiradiation drugs [1,2]. It plays an important role in hepatotoxicity protection, and is used as an adjuvant in the treatment of some kind of hepatic diseases, psoriasis and acne [3].…”
Section: Introductionmentioning
confidence: 99%
“…Prospective metabolites of o-chloropyridine, N-methylpyridine-2-mercapturic acid, pyridine-Noxide-2-mercapturic acid, 2-methylthiopyridine, 2-methylthiopyridine-N-oxide, 2-chloro-5pyridinol, and 2-chloro-4-pyridinol were synthesized in-house using methods of Talik 58 , Beak and Lee 59 , Westland et al 60 , and Kohrman et al 61 .…”
Section: J21 Chemicalsmentioning
confidence: 99%
“…However, if aniline and ethyl trifluoroacetate are very briefly kept at 235 °C, the 4,4,4‐trifluoroacetoacetanilide (or the enol‐like tautomer) is obtained. Subsequent treatment with concentrated sulfuric acid at 95 °C yields the 4‐trifluoromethyl‐2‐quinolinone 5−7 …”
Section: ‐Trifluoromethyl‐2‐quinolinones 1 By Condensation Of Ethyl mentioning
confidence: 99%